Condiciones para estudiar - Jiménez Espín, María Belén (2017)
The educational processes in Ecuador requires a better academic performance of the students, which are part the effective and efficient on learning process, that shows the practical improvement of studying habits, which allows to get skills and knowledge inside and outside the classroom; At this context, the researching is focused in to analyze how the studying conditions could development cognitive skills, whose objective is to diagnose the acquisition of abilities, improve designing new methodological techniques of researching that allowed to show, situations that gave direct orientation to generate conclusions and recommendations. It can be shown that teachers and students´ conditions tor studying should always be applied on the field of education; there are fundamental elements, internal and external, in the learning environment. Teachers express that the conditions for studying must be applied in a way that achieves high academic performance….